(untitled) (Journal of the College of Basic Education, 2023)
The Creator chose for His Prophet (may God bless him and grant him peace), honorable companions who took advantage of his knowledge, and borrowed from him: sincerity, honesty and great morals, until they were the elite of this nation and its leaders. So they strived in God with the Messenger (may God bless him and grant him peace) as the right of jihad, and carried after him the trust of informing, and from this generation the followers took, so they were the blessing that preserved the nation’s religion, at a time when worldliness began to impose itself strongly on society after religion was the center of life Its members, so they rushed with all their vigor to give things their ideal image, especially after they moved away from the actual contribution to power after the transfer of the seat of government to Damascus with the advent of the Umayyads. However, their interest was not only focused on the religious aspect, but they had a tangible impact on various aspects of life, and they were not isolated from the course of events and changes in that era.Hence the idea of the research that was devoted to investigating the impact of the jurists who lived in the Umayyad era on political life, represented by the position of the authority towards them, and their position on the authority.The research is based on what was preserved of their news, so he surrounded it, looked at it, and drew conclusions from it, without interpretation in the interpretation of the texts, or arbitrariness in the issuance of judgments.